World population prospects 1989 (Population studies ;, 1990)
Part of a UN effort to revise demographic data every 2 years, this comprehensive report contains up-to-date estimates and projections of population and other demographic variables for all countries and regions of the world. While most of the information has come from available national data, some of it has been adjusted because of deficiencies or insufficiency. The 1st section of the report provides the current demographic status of population size and growth, and fertility and mortality, as well as the major changes in the 1990 revision. Among the major findings, the world population currently stands at 5.3 billion and it is growing at a rate of 1.7% a year. Total population is expected to increase to 6.3 by the year 2000 and to 8.5 by 2025. Africa has led the world in growth rate per year (3%) the 1985-90 period, followed by Latin America (2.1%) and Asia (1.9%). Figures indicates that Africa is gradually replacing Europe as the second most populous continent after Asia. Among the largest countries, Kenya and Tanzania will register the fastest growth between 1950-2025; the Federal Republic of Germany and Great Britain have had the slowest growth. Some of the methodological changes since the 1988 revision include an introduction of new replacement-level, age-specific fertility patterns, as well as aggregation figures for life expectancy at birth. Part 2 of the report contains 17 tables listing figures on regional and national demographic variables. Some of these include total population, crude birth rate, crude death rate, total fertility rate, and infant mortality.